Individual taxpayers’ perception towards self assessment system: Sabah case - Junainah Jaidi; Norsiah Ahmad; Raman Noordin; Abdul Wahid Mohd Kassim (Faculty of Business, Economics and Accountancy, Universiti Malaysia Sabah, 2003)
Undoubtedly, economic analyses are important to understand a tax system, however in a democratic system, the taxpayer’s perception, evaluation and compliance with the tax laws are of equal importance. This study attempt to explore the taxpayers’ acceptability towards self assessment system and also to investigate an overall view of taxpayers’ perception on the present tax system. A survey was undertaken in Kota Kinabalu, Sabah, involved 195 individual salaried taxpayers. Result of the study revealed that the Malaysian taxpayers are satisfied with the present tax system. They see it as a simple and easy system. However the study also revealed that the taxpayers welcome the changing of the present system to the self assessment system. They perceived that they are ready for it. Despite of the taxpayers readiness toward self assessment system, most of the ta xpayers did not know their responsibility under the new system, moreover they also unable to compute their own tax. However most of them are interested in learning more about the Malaysian Income Tax System if they have the opportunity to do so. The taxpayers surveyed had a poor understanding of the tax laws. So that, recommendations were made to MIRB in order to increase the taxpayers knowledge and understanding of their obligation and rights as a taxpayer. The effective ways of communications and promotion of self assessment system were also suggested.